Ubiquitous Display Environments - Kuflik, Tsvi; Kruger, Antonio (Cognitive Technologies,, 2012)
Our increasingly smart environments will sense, track and model users and provide them with personalized services. We can already embed computers in everyday objects such as shirt buttons and pencils; objects of all sizes, from wristwatches to billboards, will soon incorporate high-quality flexible displays; we have improved access to wireless Internet communication; and we are now transitioning from traditional linear to targeted interactive media. The convergence of these factors -- miniaturization, display technologies, wireless communication, and interactive media -- will allow us to leave our desktop computers and move to a new radical computing paradigm, the ubiquitous display environment, where media and visual content will support a rich variety of display devices that enable users to interact with information artifacts in a seamless manner. This is one of the most exciting and important areas of technology development and this book addresses the challenge within the context of an educational and cultural experience. This is inherently a multidisciplinary field and the contributions span the related research aspects, including system architecture and communications issues, and intelligent user interface aspects such as aesthetics and privacy. On the scientific side, the authors integrate artificial intelligence, user modeling, temporal and spatial reasoning, intelligent user interfaces, and user-centric design methodologies in their work, while on the technological side they integrate mobile and wireless networking infrastructures, interfaces, group displays, and context-driven adaptive presentations. This book is of value to researchers and practitioners working on all aspects of ubiquitous display environments, and we hope it leads to innovations in human education, cultural heritage appreciation, and scientific development.